Efficacy and safety of metaraminol in critically ill patients with shock: a systematic review. (11th March 2022) - Sardaneh, Arwa Abu; Narayan, Sujita; Penm, Jonathan; Oliver, Matthew; Gattas, David; McLachlan, Andrew J.; Patanwala, Asad E.
Abstract: Aim: To assess the efficacy and safety of metaraminol infusions in comparison to other vasopressors in critically ill patients with shock with regard to hospital mortality, effect on haemodynamics (mean arterial pressure or systolic blood pressure), duration of vasopressor use, and adverse events. Data sources: A systematic review was conducted in eight electronic databases and nine trial registers from inception to 17 March 2021. Study selection: Studies included randomised or non‐randomised controlled trials, and retrospective or prospective observational studies of critically ill adult patients admitted to the intensive care unit or emergency department with shock of any aetiology and who received metaraminol via continuous infusion compared to patients who received other vasopressors. Results: Out of 1387 eligible articles, three observational studies and one controlled trial were included involving a total of 54 patients. Study patients had different types of shock including septic ( n  = 28), cardiogenic ( n  = 21), hypovolemic ( n  = 3) and neurogenic shock ( n  = 2). All studies compared metaraminol to noradrenaline and were of poor quality and high risk of bias. There was no difference in hospital mortality or effect on mean arterial pressure or systolic blood pressure between metaraminol and noradrenaline in any of the studies. None of the studies reported the duration of vasopressor use or adverse drug events such as extravasation or tissue injury. Conclusion: There is limited and low‐quality efficacy and safety data to support the use of metaraminol over other vasopressors in critically ill patients with shock. Future clinical trials are needed before this agent is routinely used in this patient population.